Mid- to Long-Term Outcomes After Deep Infections After Arthroscopic Rotator Cuff Repair - Julia K. Frank, M.D; Nikos Nadiotis; Philipp R. Heuberer, M.D; Brenda Laky, M.Sc., Ph.D; Werner Anderl, M.D; Leo Pauzenberger, M.D (Elsevier, 2020)
Purpose: To review clinical and subjective outcomes in patients with deep infections after arthroscopic rotator cuff repair. Methods: All patients in whom deep infections developed after arthroscopic rotator cuff repair at a single center between 2002 and 2016 were retrospectively reviewed. Demographic data, clinical and microbiological findings, and treatment were analyzed. Clinical and subjective outcomes included the Constant score, visual analog scale score for pain, American Shoulder and Elbow Surgeons score, and Simple Shoulder Test score. Results: Thirty patients could be identified and included in the study. The most commonly isolated pathogens were Staphylococcus epidermidis (36.7%) and Cutibacterium acnes (30.0%). In 26 of 30 patients (86.7%), the infection was treated initially with an open surgical approach, whereas 4 patients (13.3%) underwent arthroscopic revision. A transosseous rotator cuff repair could be performed in 20.0% of patients. A single reoperation was sufficient in 80% of patients, whereas 13.3% required 2 revisions and 6.7% required 3. At the final follow-up of 8.3 years (range, 4-14 years), 26 patients (1 woman and 25 men) were available for outcome evaluation. Significant improvement from the initial surgical procedure to final follow-up was detected in the Constant score (25.7 vs 65.7, P < .001), visual analog scale score for pain (7.0 vs 1.7, P < .001), American Shoulder and Elbow Surgeons score (38.0 vs 76.7, P < .001), and Simple Shoulder Test score (4.0 vs 8.3, P < .001). Conclusions: Patients with deep infections after arthroscopic rotator cuff repair showed moderate mid- to long-term outcomes. Level of Evidence: Level IV, therapeutic case series.